A mega gallbladder removed by laparoscopic cholecystectomy: a case report - Bastidas, Alexandra; Cuevas, Liliana (International Surgery Journal, 2020)
Report the case of a giant gallbladder secondary to chronic cholecystitis treated with laparoscopic cholecystectomy with no complications. The patient was a 79-year-old woman who attended the emergency department because of a long-standing abdominal pain in the right hypochondrium exacerbated in the last 2 months. Physical exam revealed fever and a sensible mass in the right flank, laboratory tests shown leucocytosis, a mild indirect hyperbilirubinemia and elevated alkaline phosphatase. Images revealed an importantly distended gallbladder with sludge, stones and hydrops associated. Antibiotic therapy was started. She ultimately underwent laparoscopic cholecystectomy. A pathological examination evidenced cholelithiasis, acute and chronic cholecystitis. Only a few cases of surgical treatment of mega gallbladders are found in the literature. It is important to recognize them in the preoperative period for an adequate surgical planning. A laparoscopic approach was successful in our case.